2014
DOI: 10.2460/javma.245.1.99
|View full text |Cite
|
Sign up to set email alerts
|

Total dietary fiber composition of diets used for management of obesity and diabetes mellitus in cats

Abstract: Diets provided a range of TDF concentrations with variable concentrations of IDF, HMWSDF, and LMWSDF. Crude fiber concentration was not a reliable indicator of TDF concentration or dietary fiber composition. Because carbohydrate content is calculated as a difference, results suggested that use of crude fiber content would cause overestimation of both carbohydrate and energy content of diets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
2
7
0
Order By: Relevance
“…Differences between manufacturer-reported maximum moisture concentrations and measured moisture concentrations in the present study were consistent with results of other studies, 26,40,41 as were differences between the reported maximum CF and measured TDF concentration. 26,28,40 In canned diets only, reported maximum CF concentration was not different than measured IDF concentration, suggesting this value could potentially be used to estimate IDF content in similar diets.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Differences between manufacturer-reported maximum moisture concentrations and measured moisture concentrations in the present study were consistent with results of other studies, 26,40,41 as were differences between the reported maximum CF and measured TDF concentration. 26,28,40 In canned diets only, reported maximum CF concentration was not different than measured IDF concentration, suggesting this value could potentially be used to estimate IDF content in similar diets.…”
Section: Discussionsupporting
confidence: 92%
“…As has been described for diets formulated to manage obesity and diabetes mellitus in cats, 40 energy density of all diets formulated for dogs with diabetes mellitus, obesity, or dietary fat-responsive disease in the present study was negatively correlated with TDF concentration. Although this is not the only factor to affect energy density, it appears to have a role in the formulation of therapeutic diets for these indications, given that there were significant differences in composition and concentration of TDF among diet categories.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…For each diet, the listed ingredients, caloric content (kcal/cup and kcal/kg), crude fiber as fed (%), crude fiber on a dry matter basis (%), moisture (%), total dietary fiber, insoluble fiber, and soluble fiber content when available were recorded [30, 31]. Actual caloric intake for each dog was recorded and compared to their calculated resting energy requirement (RER) and maintenance energy requirement (MER).…”
Section: Methodsmentioning
confidence: 99%
“…As mentioned previously, dietary fiber in cat foods can have benefits for the animals ( Davenport et al, 2008 ; Roudebush, et al, 2008 ; Owens et al, 2014 ; Linder and Parker, 2016 ; Loureiro et al, 2017 ); however, it is known to impact extrusion processing. The impacts are well described for breakfast cereals and other snacks for humans ( Mendonça et al, 2000 ; Brennan et al, 2008 ; Karkle et al, 2012a , 2012b ; Kallu et al, 2017 ; Wang et al, 2017 ).…”
Section: Discussionmentioning
confidence: 95%